TERAPI DZIKIR SEBAGAI INTERVENSI KEPERAWATAN UNTUK MENURUNKAN ANSIETAS PADA LIMFOMA NON-HODGKIN - Putrie, Azzahra; Netra Wirakhmi, Ikit (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Non-Hodgkin's Lymphoma is a type of cancer that can lead to psychological problems, particularly anxiety. Unmanaged anxiety may negatively affect physical condition and treatment outcomes. One non-pharmacological intervention that can be applied is dhikr therapy as a spiritual approach in nursing care. Objective: This study aimed to describe the application of dhikr therapy in reducing anxiety levels in patients with Non-Hodgkin's Lymphoma. Methods: This study employed a case study design using a nursing care approach, including assessment, nursing diagnosis, planning, implementation, and evaluation. The subject was a 63-year-old female patient treated in the Wijaya Kusuma Ward of Prof. Dr. Margono Soekarjo Regional Hospital with anxiety as the primary nursing problem. Dhikr therapy was administered for approximately 10 minutes as part of the nursing intervention. Results: The evaluation results showed positive changes in the patient’s psychological condition after the implementation of dhikr therapy. The patient reported better understanding of her illness and reduced feelings of anxiety and confusion. Objectively, the patient appeared calmer, more cooperative, and exhibited decreased restlessness compared to before the intervention. The patient’s response to treatment also improved. Conclusion: Dhikr therapy is effective as a non-pharmacological nursing intervention in reducing anxiety in patients with Non-Hodgkin's Lymphoma.